(untitled) (Pedagogical Horizons, 2021)
In this essay, the question is whether and to what extent similarities and differences emerged in the contemporary-political-pedagogical development of memory culture as well as memorial pedagogy in Bavaria and Austria. First of all, attention is paid to the concept of memorials and their functions and tasks, in order to make a further comparison of the two concentration camp memorials Dachau and Mauthausen. In addition to the developments of the memorials since 1945, the focus is also on political discourses in dealing with the former concentration camps. In addition, the pedagogical conceptions of the two memorials are compared and analyzed. Another aspect relates to curriculare and school book-related relevance of memorial visits.